Clinical Cases in Adolescent Dermatology - Lotti, Torello M.; Arcangeli, Fabio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is a concise practical guide designed to facilitate the clinical decision-making process in the management of adolescent skin disease. Dermatologists and general pediatricians who offer primary care to adolescents must be knowledgeable in managing dermatological problems, and this title provides insightful reviews of a number of common and rare dermatologic cases. Clinical cases are a key component in modern medical education, assisting the trainee or recertifying clinician to work through unusual scenarios using best practice techniques. Adolescent dermatology is a particularly important discipline in this regard, since it is a highly visual subject requiring the reader to describe often very subtle differences in the presentation of patients and define accurately the diagnostic and management criteria on which to base their clinical decision-making. Clinical Cases in Adolescent Dermatology concisely covers how to approach diagnosing and managing patients from 12 through 18 years of age. Each chapter focuses on a particular case and emphasizes how to make an appropriate choice when deciding which diagnostic tool or management strategy would be most suitable. Potential complications are detailed and management tips provided to enable the reader to develop a deep understanding of how approach the care of these patients within their day-to-day clinical practice. This book therefore represents an ideal up-to-date resource for all practitioners who encounter the condition as part of their everyday practice.
A red plaque on the cheek in a 12-year-old girl -- Leprosy in Pediatric age -- Localized acquired alopecia over the mental area of chin -- Multifocal erythematous plaques complicated by ulceration on the face and upper extremities in a child -- Skin pigmentation at angle of the mouth -- Vascular Lesion on the hand -- Vulvar ulcers in a young girl -- A 13 Years Old Female with Refractory Purpura -- Erythrodermic psoriasis in pediatric age -- Generalized Molluscum Contagiosum in A Young Girl -- Nail dystrophy in a teenager -- Necrotic and vesicular lesions after sun exposure -- Non-Pseudomonal Ecthyma Gangrenosum Resembling Pyoderma Gangrenosum on Malnourished Child with End Stage Renal Disease -- Subcutaneous Nodular Lesion Of The Lumbar Area -- Ecchymotic lesions on the left foot in a 14-year-old child -- Low-birthweight dwarfism with features include cranio-facial disproportion, facial dysmorphia, lateral asymmetry and clinodactyly -- Multiple papular and nodular facial lesions -- Norwegian Scabies In Patient With Down Syndrome -- A boy with reticular lesions on his waist and back -- A disseminated papulonodular eruption in a 15-Year-Old male with Aplastic Anemia -- Adolescent female with brown papules and peculiar nails -- An Unusual Coincidence of Alopecia Areata with Trichotillomania in a Child with Osteogenesis Imperfecta -- Painful Herpetiform Aphthous Ulcers In The Oral Mucosa In A 15-Year-Old Man -- A 16-year-old boy developing lesions on his tattoo -- An adolescent with recurrent eczematous lesions -- Erythema Annulare Centrifugum Mimicking Tinea Cruris on Child with Acute Myeloid Leukemia -- Painful, violaceous, woody mandibular nodule in a healthy teenager -- A teenager with refractory erythroderma -- Deep red macules in a blaschkoid distribution in an adolescent male -- Erythematous plaques with central atrophy on lower limbs in young woman -- Generalized hypopigmented macules and verrucous papules in three siblings -- Tuberous Sclerosis Complex With Clinodactyly -- A young boy with hyperpigmented and hypopigmented macules.
Keywords: Dermatology; Pediatrics; Dermatology; Pediatrics; Skin Diseases; Adolescent; Case Reports